2014
DOI: 10.1002/ece3.1343
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic relationships between body size, species richness, abundance, and energy use in a shallow marine epibenthic faunal community

Abstract: We study the temporal variation in the empirical relationships among body size (S), species richness (R), and abundance (A) in a shallow marine epibenthic faunal community in Coliumo Bay, Chile. We also extend previous analyses by calculating individual energy use (E) and test whether its bivariate and trivariate relationships with S and R are in agreement with expectations derived from the energetic equivalence rule. Carnivorous and scavenger species representing over 95% of sample abundance and biomass were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…9 of main text to this case cannot be computed analytically. Some empirical studies [10,11] found a P (m|A) similar to a log-normal. We can describe this case as P (m|A) = m −δ F 2 m A λ where F 2 (x) is such that lim x→0,∞ x j F 1 (x) = 0 ∀j.…”
Section: Alternative Forms Of P (M|a)mentioning
confidence: 95%
See 1 more Smart Citation
“…9 of main text to this case cannot be computed analytically. Some empirical studies [10,11] found a P (m|A) similar to a log-normal. We can describe this case as P (m|A) = m −δ F 2 m A λ where F 2 (x) is such that lim x→0,∞ x j F 1 (x) = 0 ∀j.…”
Section: Alternative Forms Of P (M|a)mentioning
confidence: 95%
“…Precise estimates of the scaling exponents' values are thus crucial. Empirical evidence, however, shows that they vary considerably across ecosystems [9,10,11], suggesting that exponents of scaling ecological laws are far from universal, although the power-law form proves remarkably robust ( Fig. 1).…”
mentioning
confidence: 99%
“…Aguilera et al, 2015, 2019; Fenberg et al., 2015; Fenberg & Rivadeneira, 2019; Ibáñez, Waldisperg, et al., 2019; Moreno et al., 2006). In addition, for marine vertebrates and invertebrates it has been evidenced that body size distribution shows a correlation with species richness at different spatial scales (Barneche et al., 2019; Labra et al., 2015). Particularly along the south‐east Pacific coast (SEP), latitudinal clines of body size have been detected at intraspecific level in several invertebrates (Camus et al., 2012; Ibáñez, Waldisperg, et al., 2019; Jaramilllo et al, 2017; Lardies et al., 2010; Sepúlveda et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Aguilera et al, 2015Aguilera et al, , 2019Fenberg et al, 2015;Fenberg & Rivadeneira, 2019;Ibáñez, Waldisperg, et al, 2019;Moreno et al, 2006). In addition, for marine vertebrates and invertebrates it has been evidenced that body size distribution shows a correlation with species richness at different spatial scales (Barneche et al, 2019;Labra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Off the south-central coast of Chile in the first days of January 2008, there was an intense and extensive upwelling event that involved a spatial scale of hundreds of kilometers. This produced an intrusion into the coastal area of ESSW from the oxygen minimum zone (OMZ), and produced massive mortality and beaching of fish, crustaceans and molluscs in Coliumo Bay [ 18 21 ], as well as zooplankton (see Fig 1 ). The OMZ in the Humboldt Current System is characterized by an oxygen concentration of <20 μmol kg −1 (0.5 mL O 2 L -1 ) ( e .…”
Section: Introductionmentioning
confidence: 99%